Equidade como parâmetro do justo: a passagem do logos teórico ao logos prático no raciocínio jurídico - Zakia, Maria Lucia Perez Ferres (2017)
From the complex concept of justice developed by Aristotle, the object of justice is delineated, distinguishing it from morality, with the objective of understanding the classical conception of law, considering its object, concept and sources. For this, the Aristotelian conceptions of the term "justice" are worked out: its absolute and particular, precisely political, meaning, differentiating it from domestic justice and classifying it as distributive, corrective and reciprocal. It follows the delimitation of the object of law as part of justice, the identification of its sources: natural and positive law, and finally, we come to the concept of equity as justice in the case in point and its methodological reflex in the process of appropriate application of positive law and integration of gaps. Then, it returns to the analysis of the modern conception of law, following the same methodology initially adopted, starting from the delimitation of its object, concept and sources, arriving at a diverse concept of equity assumed by the modern juridical philosophy. Finally, it is tried to demonstrate the process of return of the equity, in the classic terms, like justice in the case in concrete, to the modern juridical thought, from the material point of view, evidencing the progressive detachment of the science of the law with the society and the necessity In the construction of a legal theory that encompasses values, especially justice, and responds to the ever-changing social desires; As a methodological point of view, identifying the insufficiency of the formal logical method as the only instrument available to the judge and the progressive introduction of the dialectical process of justice construction case by case and rhetoric as an instrument of motivation and persuasion of the judge, without neglecting what is necessary Justice and legal certainty. As a conclusion, it is tried to demonstrate how the process of absorption of the equity in the classic molds caused new contours to the legal science, reflecting in the concept of law, in the identification of its sources, in the object and in the methodological aspect